Pengaruh Relationship Efforts terhadap Relationship OutcomesPendengar Radio Ratu FM Jember - Musmedi, Didik Pudjo (Universitas Jember, 2010)
This study aims to determine: (a) the relationship effort influence directly or indirectly on relationship outcomes, and (b) satisfaction influence on trust. In this research relationship effort model that includes four types of independent variables are communication, personalization, preferential treatment and rewarding. And the dependent variable in this study is the satisfaction and trust of listeners. In this study, the sampling technique is done by accidental sampling with amount of sample as much 88 respondents and methods of data analysis used was path analysis. The result of this research are: (a) communication significantly influence directly on satisfaction and trust of listeners and communication influence the trust through satisfaction of listeners, (b) preferential treatment significantly influence directly on satisfaction and trust of listeners and preferential treatment influence on the trust through satisfaction of listeners, (c) Rewarding significantly influence directly on satisfaction and trust of listeners and rewarding influence trust through satisfaction of listeners, (d) Personalization significant influence directly on satisfaction and trust with listeners and personalization influence trust through satisfaction of listeners and ( e) Satisfaction significant influence on the trust of listeners. Keywords: Relationship Efforts, Relationship Outcomes and Path Analysis